Discovery of a new species of Trieces (Hymenoptera: Ichneumonidae: Metopiinae) questioning the traditional delimitation between Trieces and Chorinaeus - Mazón, Marina; Bordera, Santiago (Zootaxa, 2020)
In this paper a new species of the Metopiinae genus Trieces Townes from Spain, Trieces confusus sp. nov., is described and illustrated. This species has diagnostic characters of both Trieces and the genus Chorinaeus, and we provide a brief discussion of the implications for the current delimitation of these genera.